One-Step Nonaqueous Synthesis of Pure Phase TiO2 Nanocrystals from TiCl4 in Butanol and Their Photocatalytic Properties. (14th May 2011) - Cao, Tieping; Li, Yuejun; Wang, Changhua; Shao, Changlu; Liu, Yichun
Abstract : Pure phase TiO2 nanomaterials were synthesized by an autoclaving treatment of TiCl4 with butanol as a single alcohol source. It was found that the control of molar ratio of TiCl4 to butanol played an important role in determining the TiO2 crystal phase and morphology. A high molar ratio of TiCl4 to butanol favored the formation of anatase nanoparticles, whereas rutile nanorods were selectively obtained at a low molar ratio of TiCl4 to butanol. Evaluation of the photocatalytic activity of the synthesized TiO2 was performed in terms of decomposition of organic dye rhodamine B under ultraviolet irradiation. It turned out that the as-synthesized TiO2 crystallites possessed higher photocatalytic activities toward bleaching rhodamine B than Degussa P25, benefiting from theirhigh surface area, small crystal size as well as high crystallinity.